2018
DOI: 10.1021/acs.jpcc.7b10467
|View full text |Cite
|
Sign up to set email alerts
|

Ion Valence and Concentration Effects on the Interaction between Polystyrene Sulfonate-Modified Carbon Nanotubes in Water

Abstract: We use molecular dynamics simulations and the adaptive biasing force method to evaluate the potential of mean force between two carbon nanotubes (CNTs), with each surface modified by an adsorbed sodium-polystyrene sulfonate (Na-PSS) polyanion, in aqueous electrolyte media. Changes in the electrolyte concentration and counter-ion valence can lead to qualitative changes in the interactions between polyelectrolyte-modified CNTs. We show that in the presence of monovalent NaCl salt, a long-range screened electrost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 62 publications
4
7
0
Order By: Relevance
“…However, with the addition of 0.5 M NaCl electrolyte, the surface potential on the cuboid silica has decreased to approximately 0.1 V, as a result of enhanced screening of its surface charge by the condensation of Na + counter-ions. This result is consistent with the idea of electrostatic screening of the surface potential with the addition of salt 42 and consequently, a decrease in the screening length so-called Debye length. The surface potentials observed with respect to spheroid and cuboid geometry at other pH conditions can be seen in Fig.…”
Section: Electrostatic Potential Distributionsupporting
confidence: 91%
“…However, with the addition of 0.5 M NaCl electrolyte, the surface potential on the cuboid silica has decreased to approximately 0.1 V, as a result of enhanced screening of its surface charge by the condensation of Na + counter-ions. This result is consistent with the idea of electrostatic screening of the surface potential with the addition of salt 42 and consequently, a decrease in the screening length so-called Debye length. The surface potentials observed with respect to spheroid and cuboid geometry at other pH conditions can be seen in Fig.…”
Section: Electrostatic Potential Distributionsupporting
confidence: 91%
“…Thus, the results obtained from our simulations are in qualitative agreement with our experimental observations of large negative zeta potentials on PSS-modified MWCNT surfaces. The experimental results are also in agreement with our recent atomistic simulation studies [44] on interactions between two CNT/Na-PSS complexes in water, where we explicitly showed using free energy calculations that the negative potential leads to a long-range repulsive interaction energy between two Na-PSS modified CNT. Further, we have also demonstrated that addition of an electrolyte leads to a screening of the electrostatic interaction between the two CNT/Na-PSS complexes.…”
Section: Zeta Potential Measurement and Uv-vis Spectroscopic Analyssupporting
confidence: 91%
“…[ 43 ] A detailed description of the simulation setup and calculations can be found in our recent simulation work investigating ionic effects on the stability of Na‐PSS‐modified CNT dispersions. [ 44 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CHARMM force field was used to model all interatomic interactions, and the TIP3P model was used to describe water molecules. The detailed description of the simulation setup and the method adopted are provided in the Supporting Information of Section S1, and the same information discussed extensively can be found in publications from our group. …”
Section: Simulation Methodsmentioning
confidence: 99%